Study of various aspects of firearm injuries on dead bodies brought from rural and urban areas of Patna city. - Ranjan, Ranjay Kumar; Aakanksha; Mishra, Mukesh Kumar; Rajiv Ranjan Das (Student’s Journal of Health Research Africa, 2024)
Introduction Firearm injuries are a global public health problem and pose therapeutic challenges all over the world. Civilian firearm injuries are increasing globally. Increased incidence of firearm injuries in developing countries has been attributed to poverty, unemployment, political instability, lack of education, and unequal distribution of wealth. Use of firearms and explosives for homicide is a worldwide phenomena. This is due to increasing number of urban terrorism, robberies, dacoity, rioting, political motivation, smuggling of drugs, personal and group rivalry, quarrel over property, caste feuds and the like. Materials and Methods The Retrospective observational study was carried out 65 victims of fatal firearm injury of different age groups, brought to the mortuary for autopsy in the Department of FMT, NALANDA MEDICALCOLLEGE, Patna between 1st November 2018 to 31st October 2020. The datas were recorded according to standard proforma and analysed. Results : The most common age group affected was 31-40 years and had completed 12th Standard to Graduation level of qualification Most of the victims approximately 33.84%, were unemployed. The commonest cause behind the firearm injury was personal rivalry (40%) followed by looting & dacoity( 24.62% ). Among the cases of firearm injuries, in 92.31% cases were caused by rifled firearms and common target of firing was the head. Conclusions: Firearm injuries have become a major cause of morbidity and mortality among young males in our society. The homicidal attack was carried out with the motive of personal or political rivalry or dacoity and robbery, mostly using the rifle firearms. High rates of unemployment and poverty have been reported to be responsible for increasing incidence of youth restiveness, armed robbery and associated firearm injuries in our society.